THE ROLE OF MICROLEARNING IN ENHANCING LEARNING ENGAGEMENT AMONG GEN Z STUDENTS - Faridah Mohd Shah; Mimi Zarina Bakri; Suali@Suhailie Bakrin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Amidst swiftly changing educational demands, microlearning has surfaced as an effective method to boost learning involvement, especially for Generation Z (Gen Z) learners. Generation Z, recognized for their digital literacy and inclination for brief, on-demand content, is progressively attracted to microlearning as a productive and effective method for gaining knowledge. This research examines the role of microlearning on enhancing learning engagement for Gen Z students through short, targeted lessons that cater to their limited attention spans and capacity for multitasking. A quantitative research approach was employed involving 150 university students in Kota Kinabalu, Sabah, Malaysia. Data were collected using a structured online questionnaire and analyzed using SPSS Version 26. The findings revealed a strong positive correlation between microlearning and learning engagement (R = 0.643, p < 0.001), with 41.3% of the variance in engagement explained by microlearning practices. Additionally, students who used microlearning frequently demonstrated significantly higher levels of self-directed learning (p = 0.025), adaptability (p = 0.008), knowledge retention (p = 0.000), and overall learning satisfaction (p = 0.000). Among the components assessed, interactive and personalized microlearning formats showed the strongest effects. These results affirm that microlearning is a highly effective approach to meet the learning preferences of Gen Z students. The study offers valuable insights for educators and policymakers aiming to integrate digital microlearning strategies to improve student engagement, adaptability, and academic outcomes in higher education contexts.